The role of training in Algerian universities in equipping students with certain professional skills: A comparative study between the classical system and the LMD system. - حسام ير; حملاوي عامر (sports creativity, 2025)
Scientific research and technological development aim to achieve the economic, social, cultural, scientific, and technological development of any country. Algeria was among the countries that paid attention to this field. The Ministry of Higher Education and Scientific Research set a goal of comprehensive and profound reform of higher education by establishing a new structure for higher education accompanied by improvements to pedagogical programs. This aims to provide quality training for better professional integration of university students, which is a fundamental basis for determining the extent to which educational goals are achieved. The student entering the field of education, i.e., the professor, has been subjected to new and multiple duties and responsibilities due to the great changes the world is witnessing today in all areas of life, in order to keep pace with the times and deal with the challenges of the future. The new roles have made the professor no longer a mere instructor but a leader of his students to reach the peaks of creativity and innovation, a guide to sources of knowledge, a coordinator of educational processes, and an evaluator of educational outcomes. Thus, his roles have multiplied, so he is now expected to be a professor, an educator, a mentor, a psychological observer, a social leader, an administrative organizer, a technical engineer, and a researcher. Scientifically (06, p. 262), the professor is also required to be proficient in all the professional skills and competencies upon which the planned objectives are based. Furthermore, their roles have expanded to include diagnosing education, motivating students, managing the learning environment, and organizing learning experiences (09, p. 03). To train professors according to the demands of the job market, the university must dedicate all its resources and capabilities to ensure the development of reliable professors who can contribute to the fundamental goals that the national education sector aspires to achieve within the framework of reforming the educational system. This includes curbing the decline in the overall level of education and the efficiency of the educational system, as well as identifying and developing the necessary tools and resources to implement a number of measures aimed at improving and training staff and enhancing educational resources. Physical education and sports, as part of the educational process, reflect the philosophy of society and its development as a social process. It works to improve the reality of its educational process by ensuring good preparation of its teachers in various aspects. Therefore, the physical education teacher must be at the highest level of professional and educational preparation, armed with many of the skills necessary to perform his assigned duties, especially in this era, which is described as the era of scientific explosion and specialization.